Michael Faraday en die letterlike lesing van twee ‘boeke’ van God: 'n Gevallestudie oor verhouding tussen geloof en wetenskap1 - Botha, M. Elaine (Koers, 1993)
The cognitive historical approach to the history of science provides a methodological approach which makes it possible to take into account most of the factors which were constitutive in the formation of scientific meaning in scientific concept formation. In this article this approach is linked with a methodology of metaphorical hermeneutics in order to determine the role played by religious factors in the meaning of scientific concepts. Contrary to traditional approaches in which religious factors are primarily seen as confessional in nature, the term religious is utilized here to identify those absolute presuppositions which fulfil a controlling or regulative function in scientific concept formation and theorizing. 'This approach is applied to a case study of the relationship of faith and science in the work of the nineteenth century British physicist, Michael Faraday. This approach provides an analysis of the change in conceptual structure which the concept of force undergoes in a transition from a mechanistic to a dynamistic metaphysical framework. In this analysis attention is also given to the distinction between confessional religious factors, metaphysical frameworks, meta-scientific principles and theories.